A New Alkylation of Aryl Alcohols by Boron Trifluoride Etherate - Jumbam, Ndze Denis (Molecules, 2019)
The ethylation of aryl alcohols by an ethyl moiety of boron trifluoride etherate is described. The reaction proceeded cleanly and afforded good yields of the corresponding aryl ethyl ethers. It tolerated the presence of functional groups such as aryl, alkyl, halogens, nitro, nitrile, and amino. However, the presence of amino or nitro groups ortho to a hydroxyl group of an aryl compound drastically reduced the yields of the anticipated products due to the chelation of the aforementioned functional groups with boron trifluoride etherate. A nitrogen atom in the aromatic ring system, as exemplified by hydroxypyridine and 8-hydroxyquinoline, completely inhibited the reaction. Resorcinol, hydroquinone, and aryl alcohols with aldehyde functions decomposed under the reaction conditions.